Kosmologi Sekala-Niskala Refleksi Estetika Lukisan I Nyoman Sukari - I Gede Arya Sucitra; Rr. Siti Murtiningsih (Universitas Gadjah Mada, 2020)
Philosophical reflection provides an understanding of all the activities of various components of the work of human works as a related entity in a network with one another. Language, myth, religion, and art and artists as human creators are not unrelated, but rather integrated into a single bond.I Nyoman Sukari as an artist, has a pluralistic and multicultural variety of artistic achievements bringing all the charm, experience, mystery, stories, mythology of Bali and Java inherent in his body, mind, and soul. The philosophical issues in Sukari's paintings are full of Balinese locality values and their multicultural nature; religiosity, mythology, history, scale, tradition art, cross-culture, and contemporary or globalization issues become more complex and multi-layered in aesthetic and metaphysical terms.In this article, I will investigate and study with a hermeneutic-metaphysical approach; what is the nature of the art for I Nyoman Sukari, how far the basic principles of Hindu aesthetics reflect in his art, how Sukari understands the world of metaphysics and then interprets all inner and worldly issues (Sekala-niskala), how to negate Hindu-Balinese philosophy and the contemporary world to give birth the narratives of spirituality through painting with metaphors and symbolizations. Keywords: Metaphysics, Painting, Hindu-Balinese Philosophy, Aesthetics, Hermeneutics.